NrF2/ARE and NF-κB pathway regulation may be the mechanism for lutein inhibition of human breast cancer cell. (April 2018) - Chang, Jingzhi; Zhang, Yuxia; Li, Yichuan; Lu, Kun; Shen, Yongjie; Guo, Yali; Qi, Qingfeng; Wang, Mingchen; Zhang, Shanfeng
Aim: Though lutein can inhibit cancer cell proliferation via alleviating oxidative injury, the molecular mechanisms of lutein involvement in the NrF2/antioxidant response element (ARE) and NF-κB pathways remain poorly understood.Materials & methods : MTT, flow cytometry, quantitative real-time PCR (qRT-PCR) and western blot assays were performed.Results: After treatment with lutein, breast cancer cell proliferation was significantly decreased in a dose-dependent manner. Lutein induced nuclear translocation and protein expression of NrF2, improved the expression of cellular antioxidant enzymes and attenuated reactive oxygen species levels. Moreover, lutein treatment decreased NF-κB signaling pathway related NF-κB p65 protein expression.Conclusion: The effect of lutein antiproliferation was mediated by activation of the NrF2/ARE pathway, and blocking of the NF-κB signaling pathway.